GREEN LOGISTICS IN LIFE CYCLE MANAGEMENT: THE THEORETICAL ASPECT - Nehme, Mohamad; Brin, Pavlo; Iskandarani, Layal (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2022)
Green Logistic, Life Cycle Management and corporate social responsibility concepts are playing increasingly significant roles in reaching sustainable outcomes on the economic and social and ecological sides. Since governments and manufacturer globe are not able to curb the economic and ecological alarming consequences for the 21 centuries as inflation and pollution. There is a need to understand that Green Logistic and Life Cycle Management must be emphasized by all element of supply chain management, starting from supplier of raw materials, passing through various stakeholders and ending with customers, all must share their responsibilities. Through a descriptive analysis for the secondary data and literature review, the papers concluded that sustainability could be achieved just if all element of supply chain management interact efficiently and share balanced responsibilities. The world today is facing economic, environmental and social challenges, caused by globalization. This has led to increased consumption, and thus increased production and flows of goods and commodities around the world. Industrial and technological revolutions have exacerbated environmental problems such as global warming and greenhouse gases that are beyond the control of governments to curb. The international community, represented by the United Nations Council and other international organizations, is working to take measures to confront these challenges. The academic community is also developing models and mechanisms to improve green logistics operations in the industrial and service sectors through design, planning, implementation, and arbitration models. The article presents the analysis of the theoretical foundations of life cycle management; the analysis of the latest publications in corporate social responsibility and life cycle management was carried out, the role of green logistics in ensuring the sustainable development of the enterprise was investigated. Based on the research results, a sustainable value chain model is presented by combining elements with green logistics tools.